2022
DOI: 10.1002/chem.202202379
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Substrate Oxidation in Lytic Polysaccharide Monooxygenases: Insight from Theoretical Investigations

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are copper enzymes that today comprise a large enzyme superfamily, grouped into the distinct members AA9-AA17 (with AA12 exempted). The LPMOs have the potential to facilitate the upcycling of biomass waste products by boosting the breakdown of cellulose and other recalcitrant polysaccharides. The cellulose biopolymer is the main component of biomass waste and thus comprises a large, unexploited resource. The LPMOs work through a catalytic, oxidative reaction whose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 138 publications
(673 reference statements)
1
7
0
Order By: Relevance
“…The spin-coupled open-shell singlet minimum 1 IC2 is at −13.3 kcal/mol, with Cu–O and O–O distances of 1.90 and 2.63 Å respectively. The geometry of 3 IC2 at the triplet spin state is nearly identical to 1 IC2, and 2.7 kcal/mol more stable, which is in agreement with previous reports on computational modeling of the Cu­(II)-oxyl in LPMOs. ,,, …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The spin-coupled open-shell singlet minimum 1 IC2 is at −13.3 kcal/mol, with Cu–O and O–O distances of 1.90 and 2.63 Å respectively. The geometry of 3 IC2 at the triplet spin state is nearly identical to 1 IC2, and 2.7 kcal/mol more stable, which is in agreement with previous reports on computational modeling of the Cu­(II)-oxyl in LPMOs. ,,, …”
Section: Resultssupporting
confidence: 90%
“…The postulated Cu­(II)-oxyl intermediate is generated by a barrierless hydrogen-atom transfer (HAT) in which the hydroxyl radical abstracts a hydrogen from the copper-bound hydroxide to form water. It is worth mentioning that other computational studies also have shown that this step has a small , or vanishing barrier, as pointed out by Hagemann and Hedegård . The spin-coupled open-shell singlet minimum 1 IC2 is at −13.3 kcal/mol, with Cu–O and O–O distances of 1.90 and 2.63 Å respectively.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…This powered computational analysis at the multiconfigurational perturbation theory (CASPT2) level to address the reliability of the DFT-predicted spin-state gaps [ 92 ]. All these high-level computational works have been very recently collected in an excellent and comprehensive review by Hagemann and Hedegård, hence we address the reader to [ 93 ] for details about LPMO electronic structure, mechanistic insights, and role of the Cu second coordination sphere seen from a computational perspective.…”
Section: Degradation Of Polysaccharides By Lpmomentioning
confidence: 99%